Broken Hearts and Battered Lives: Adverse and Abusive Life Histories and Externalized Responses to Anger as Pathways to Illicit Drug Use Among Incarcerated Women. Issue 3 (27th May 2018) - Jones, Melissa S.; Sharp, Susan F.; Worthen, Meredith G. F.
Abstract : Most incarcerated women suffer from adverse and abusive life histories, including adverse childhood experiences (ACEs), such as sexual, physical, emotional abuse, and neglect, and intimate partner violence (IPV). In addition, many have difficulties regulating their anger expression and most participate in illicit drug use. Although many have offered explanations for these relationships, the current study is among the first to utilize an integrated feminist pathways and general strain theory (GST) approach to explain them. Using data from a stratified random sample of all incarcerated women in Oklahoma ( N = 441), we explore the linkages between ACEs, IPV, the externalized expression of anger, and heavy illicit drug use. Our findings indicate that childhood physical and sexual abuse are significantly associated with externalized responses to anger. However, the effects of childhood adversities, particularly sexual abuse, on heavy illicit drug use are mediated by externalized responses to anger suggesting that anger plays a significant role in women's pathways to illicit drug use. In contrast, and somewhat surprisingly, being a victim of IPV was negatively related to externalized responses to anger and not significantly related to illicit drug use. Implications for the importance of utilizing an integrated feminist pathways and GST approach in future research are offered.